2017
DOI: 10.1038/nnano.2016.303
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualization of perforin nanopore assembly

Abstract: Perforin is a key protein of the vertebrate immune system. Secreted by cytotoxic lymphocytes as soluble monomers, perforin can self-assemble into oligomeric pores of 10-20 nm inner diameter in the membranes of virus-infected and cancerous cells. These large pores facilitate the entry of pro-apoptotic granzymes, thereby rapidly killing the target cell. To elucidate the pathways of perforin pore assembly, we carried out real-time atomic force microscopy and electron microscopy studies. Our experiments reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
128
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(148 citation statements)
references
References 48 publications
19
128
0
1
Order By: Relevance
“…[22] In order to efficiently kill a bacterium, the MAC needs to be generated by surface-bound C5 convertases. [55,56] The shape of MAC pores that were visualized by AFM seemed consistent with the cryo-EM structures that were generated with purified MAC components. Whereas C5 convertases were thought to only be essential to trigger MAC formation via the conversion of C5 into C5b, this study revealed that the role of C5 convertases extends beyond this conversion of C5.…”
Section: Bacterial Killing By the Mac Requires Local Mac Assembly By supporting
confidence: 61%
“…[22] In order to efficiently kill a bacterium, the MAC needs to be generated by surface-bound C5 convertases. [55,56] The shape of MAC pores that were visualized by AFM seemed consistent with the cryo-EM structures that were generated with purified MAC components. Whereas C5 convertases were thought to only be essential to trigger MAC formation via the conversion of C5 into C5b, this study revealed that the role of C5 convertases extends beyond this conversion of C5.…”
Section: Bacterial Killing By the Mac Requires Local Mac Assembly By supporting
confidence: 61%
“…In the neutral pH of the extracellular space perforin can bind to the target cell membrane and in the presence of Ca 2+ the monomers aggregate and form pores in the membrane (Figure ) . These ring‐shaped pores have a structure equivalent to a transmembrane channel with a pore lumen of 13–20 nm that may even coalesce into larger pores by recruiting additional perforin oligomers . As granzyme B has a stokes radius of 5 nm, it should be able to enter the target cell directly through the perforin pores, which was demonstrated in recent studies .…”
Section: Nk Cell Degranulation and Entry Of Granzymes Into The Targetmentioning
confidence: 90%
“…91 These ring-shaped pores have a structure equivalent to a transmembrane channel with a pore lumen of 13-20 nm 17 that may even coalesce into larger pores by recruiting additional perforin oligomers. 92 As granzyme B has a stokes radius of 5 nm, it should be able to enter the target cell directly through the perforin pores, 93 which was demonstrated in recent studies. 94,95 As an alternative mechanism of granzyme entry into target cells, it was proposed that granzymes are taken up by the target cell via endocytosis.…”
Section: Nk Cell Degranulation and Entry Of Granzymes Into The Targetmentioning
confidence: 93%
“…Pore growing mechanisms without the vertical collapse of poreforming proteins have been described for members of the membrane attack complex/perforin (MACPF) family (Lukoyanova et al, 2015;Metkar et al, 2015;Leung et al, 2017), whereas a prepore-to-pore transitions associated with a vertical collapse have been reported for cholesterol-dependent cytolysins (CDCs; Czajkowsky et al, 2004;Tilley et al, 2005;Leung et al, 2014;van Pee et al, 2016). To see whether a vertical collapse is associated with the assembly and pore-forming of GSDMD Nterm oligomers, we analyzed the time-lapse AFM topographs for the heights of the oligomers protruding from the surface of the lipid membrane.…”
Section: Gsdmd Nterm Oligomers Grow Pores Without Vertical Collapsementioning
confidence: 99%